Cold crematorium : reporting from the land of Auschwitz - Debreczeni, József, 1905-1978 (St. Martin's Press, an imprint of St. Martin's Publishing Group, 2023)
"The first English language edition of a lost memoir by an Auschwitz survivor, offering a shocking and deeply moving perspective on life within the camps. When József Debreczeni, a prolific Hungarian-language journalist and poet, arrived in Auschwitz in 1944, his life expectancy was forty-five minutes. This was how long it took for the half-dead prisoners to be sorted into groups, stripped, and sent to the gas chambers. He beat the odds and survived the "selection," which led to twelve horrifying months of incarceration and slave labor in a series of camps, ending in the "Cold Crematorium"-the so-called hospital of the forced labor camp Dörnhau, where prisoners too weak to work awaited execution. But as Soviet and Allied troops closed in on the camps, local Nazi commanders-anxious about the possible consequences of outright murder-decided to leave the remaining prisoners to die. Debreczeni survived the liberation of Auschwitz and immediately recorded his experiences in Cold Crematorium, one of the harshest, most merciless indictments of Nazism ever written. This haunting memoir, rendered in the precise and unsentimental prose of an accomplished journalist, is an eyewitness account of incomparable literary quality. It was published in the Hungarian language in 1950, but it was never translated, due to Cold War hostilities and rising antisemitism. More than 70 years later, this masterpiece that was nearly lost to time is now being published in more than 15 different languages for the first time, and will finally take its rightful place among the greatest works of Holocaust literature"--